The impact of technology-based learning media on students’ interests in Christian religious education - Daulat Marulitua Tambunan; Iskandar, Ferdinand (Journal of Educational Management and Instruction (JEMIN), 2024)
The increasing role of technology in education has prompted an examination of its effects on student learning interest. This study aimed to assess the impact of technology-based learning media on students' interest in Christian Religious Education. The research utilized an experimental design with a pretest-posttest control group. The sample consisted of 60 students from high school of Tunas Karya, Kelapa Gading, Jakarta Indonesia, equally divided into control and treatment groups. Data were collected using pre- and post-treatment interest tests. Data analysis was conducted using analysis of variance. The results revealed that technology-based learning media significantly enhanced students' interest in learning Christian Religious Education. The findings suggest that integrating technology-based learning media into the curriculum can effectively boost students' engagement and interest in the subject. These results have important theoretical implications, highlighting the potential of technology in educational settings, and practical implications for educators seeking to improve student engagement in religious education.